A Skin‐Mountable Hyperthermia Patch Based on Metal Nanofiber Network with High Transparency and Low Resistivity toward Subcutaneous Tumor Treatment. (17th January 2022) - Wang, Qi; Sheng, Hongwei; Lv, Yurong; Liang, Jie; Liu, Yan; Li, Na; Xie, Erqing; Su, Qing; Ershad, Faheem; Lan, Wei; Wang, Jing; Yu, Cunjiang
Abstract: A wearable hyperthermia device that allows for tumor treatment without interfering with daily activities is of clinical and social significance. However, the wide adaptation of local hyperthermia from such wearable devices in clinical practice has been hindered mainly due to several critical challenges in existing hyperthermia devices, such as the contradiction of high electrical conductivity and high optical transparency of the device while in a thin, deformable format. Here a soft, skin‐mountable, hyperthermia patch (HTP) is reported with unusual optical and electrical characteristics based on unidirectional silver nanofibers (AgNFs) network with low‐voltage operation and uniform heating even under mechanical deformation. The patch presents both high electrical conductivity and highly optical transparency simultaneously thus allowing real time inspection of the subcutaneous tumor treatment and skin response during the treatment. The unidirectional nature of the AgNFs network renders the key features of high optical transparency, low electrical resistivity, excellent electrothermal performances, and mechanical deformability. Effective treatment of subcutaneous tumors in mice is demonstrated with the skin worn HTP while the skin response is visually tracked. Systematic studies reveal the physiological mechanisms of Notch signaling in inducing tumor cell apoptosis. Abstract : A soft, skin‐mountable, hyperthermia patch (HTP) that combines broad‐spectrum transparency and excellent electrothermal performances is developed based on a unidirectional silver nanofibers network. The hyperthermia patch allows to monitor skin response while administering treatment. Hyperthermia treatment for subcutaneous tumors are demonstrated based on mice models.